A far-flung life : a novel - Stedman, M. L. (2026)
Remote Western Australia, 1958: here, for generations, the MacBrides have lived on a vast sheep station, Meredith Downs. It is a million acres, an ocean of arid land. On an ordinary day, on a lonely road, under the unending blue sky, patriarch Phil MacBride swerves to avoid a kangaroo. In seconds the lives of the entire MacBride family are shattered. And then, tragedy revisits when a twist of consequences claims the life of one sibling, and leads another to give up everything for the sake of an innocent child. Matt, the youngest MacBride, is plunged into a moral and emotional journey for which there is no map, no guide. The secrets at the heart of this gutting and beautiful story force him to choose between love and duty, sacrifice and happiness.